2020
DOI: 10.1088/1748-605x/ab6300
|View full text |Cite
|
Sign up to set email alerts
|

The use of muscle extracellular matrix (MEM) and SCPC bioceramic for bone augmentation

Abstract: Background: Bone augmentation is a challenging problem in the field of maxillofacial surgery. Objective: In this study, we prepared and evaluated muscle extracellular matrix (MEM) after adding silica calcium phosphate composite (SCPC) seeded with human bone marrow mesenchymal cells (hBMSCs). We then investigated bone augmentation in vivo using the prepared MEM-SCPC. Materials and Methods: hBMSCs were seeded on MEM-SCPC, and MEM was characterized. Calvarial bone grafts were prepared using nude mice (n = 12) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 60 publications
0
19
1
Order By: Relevance
“…However, our findings showed analogous results in both groups with a greater percentage of viability on Day 7 compared to Day 3, with an increase of up to 1.5-fold. This was in contradiction with Al-Fotawi et al’s result, which demonstrated clear variance in cell proliferation rate between the experimental and control groups ( Al-Fotawi et al, 2020 ). More importantly, this study proves the osteogenic potential after recellularization through early and late phases of osteogenic differentiation and maturation.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, our findings showed analogous results in both groups with a greater percentage of viability on Day 7 compared to Day 3, with an increase of up to 1.5-fold. This was in contradiction with Al-Fotawi et al’s result, which demonstrated clear variance in cell proliferation rate between the experimental and control groups ( Al-Fotawi et al, 2020 ). More importantly, this study proves the osteogenic potential after recellularization through early and late phases of osteogenic differentiation and maturation.…”
Section: Discussioncontrasting
confidence: 91%
“…Accordingly, our results confirmed the reduced antigenicity of DSMG, allowing for proper cell proliferation. Al-Fotawi et al (2020) exhibited a comparable cell proliferation rate using similar scaffolds and decellularization protocols. However, our findings showed analogous results in both groups with a greater percentage of viability on Day 7 compared to Day 3, with an increase of up to 1.5-fold.…”
Section: Discussionmentioning
confidence: 93%
“…15 Graph comparing the mean bone thickness in all the tested groups with the thickness of native non-operated bone (100 µm). A significant difference was found at p value < 0.05 upregulated bone sialoprotein associated with cell proliferation [7]. The upregulation of OCN and OPN expression by SCPC confirms its important role in promoting osteogenesis within the DSM/SCPC scaffold and at the interface with host bone.…”
Section: Discussionmentioning
confidence: 65%
“…These structure features of SCPC have been correlated to the significantly higher controlled dissolution rate of Si, rapid bone regeneration and graft resorption compared to bioglass in vivo 33 . Several other clinical and animal studies have demonstrated near complete resorption of SCPC in bone defects and that the resorption is associated with bone regeneration and maturation 28‐30,32,35‐39 in the time frame ideal for dental implant placement. The SCPC resorption and bone regeneration increased as the silica content in SCPC increased from 29.2 to 63.7 mol% 34 .…”
Section: Discussionmentioning
confidence: 98%